Transformasi budaya belajar dan mengajar di era merdeka belajar: perspektif fenomenologis - Ahmadi, Anas (Fakultas Sastra Universitas Negeri Malang, 2022)
This article aims to explore the transformation of learning and teaching culture in the era of independent learning through a phenomenological perspective. This article describes two main things in the transformation of learning and teaching culture. Firstly, the transformation of autonomous, freedom, digitized, and internationalized student learning culture. Secondly, the transformation of teacher culture in the era of free learning, namely being an educator must be independent in ideas and actions. In this case, an educator must have bright, creative, innovative ideas, and give independence to students. Both, both students and educators must collaborate in carrying out freedom education. Not only that, the government as a policy maker must also fully support freedom learning.